Informal Collateral Consequences - Logan, Wayne A. (2013)
After a thirty-year punitive binge, the nation is in the process of awakening to the vast array of negative effects flowing from its draconian crime control policies. The shift is perhaps most evident in the realm of corrections, which since the early 1980s has experienced unprecedented population growth. Driven by a number of factors, not the least of which is the enormous human and financial cost of mass incarceration, policy makers are now shrinking prison and jail populations and pursuing cheaper non-brick-and-mortar social control options. This Essay examines another facet of the shift: increasing concern over collateral consequences, the many ostensibly non-penal sanctions attaching to convictions, which have proliferated in recent years and impose disabilities that often dwarf in personal significance the direct consequences of conviction, such as imprisonment. Long the focus of critical scholarly commentary, collateral consequences recently drew the attention of the Supreme Court in its landmark decision Padilla v. Kentucky holding that defendants have a Sixth Amendment right to be informed of a collateral consequence (in Padilla, deportation) attaching to a guilty plea. Further testament to the national concern, the American Bar Association is now compiling a comprehensive inventory of collateral consequences imposed nationwide, casting in bold relief the many “invisible punishments” to which convicted individuals are subject